(untitled) (Baghdad Science Journal, 2012)
Bacterial contamination of AL-Habania and AL-Tharthar reservoirs were studied during the period from February 2001 to January 2002, samples were collected from four stations in AL-Habania reservoir (AL-Warrar, AL-Theban regulator, middle of the reservoir and the fourth was towards AL-Razzaza reservoir) and from two stations at AL-Tharthar reservoir (Ein AL-Hilwa and the middle of the reservoir). Coliform bacteria, faecal Coliforms, Streptococci, faecal Streptococci and total count of bacteria were used as parameters of bacterial contamination in waters of both reservoirs through calculating the most probable number. Highest count of Coliform bacteria (15000 cell/100ml) was recorded at Ein AL-Hilwa and lowest count at AL-Theban regulator and middle of AL-Tharthar reservoirs and reached (400 cell/100ml), faecal Coliform bacteria ranged between less than (300 cell/100ml) to (2300 cell/100ml). Total Streptococci ranged between less than (300 cell/100ml) to (24000 cell/100ml), faecal Streptococci ranged between less than (300 cell/100ml) to (900 cell/100ml). Total bacterial count showed variable values due to ecological changes at the stations of study which reached (3980 cell/ml) in the forth station towards AL-Razzaza reservoir and was declined to (580 cell/ml) at the middle of AL-Tharthar reservoir. Results were discussed in the research text.